Privacy, CCTV, and School Surveillance in the Shadow of Imagined Law. Issue 2 (June 2016) - Perry‐Hazan, Lotem; Birnhack, Michael
Abstract : How do managers make decisions that affect human rights of other people? The article examines one such case: the decision‐making process of Israeli school principals in installing Closed Circuit TV (CCTV) systems in schools. One unexpected source that principals relied on was that of imagined law: they wrongly assumed that there was a law that guided them in the matter. The deployment of CCTV systems in Israeli schools is relatively new and takes place at an accelerated pace. School principals are the ones that make the decision about introducing such systems into their schools. The study traced and explored this process. Based on semi‐structured interviews, the findings portray a picture of partial isomorphism among schools. We frame the findings within institutional theory, which differentiates between exogenous and endogenous sources of decision‐making. Most school principals relied on endogenous sources that were shaped by practical considerations and their own perceptions as to security, privacy, and education. Yet, the interviews indicate an additional and surprising source of organizational decision‐making: imagined law. Some of the principals assumed the existence of specific legal rules. The principals did not search for professional guidance, and did not consult others. Instead, they filled the imagined law with endogenous sources, namely, their own perceptions.